(Retracted) Motivasi Berprestasi sebagai Mediasi pada Hubungan Antara Dukungan Sosial dan Keterlibatan Siswa Di Sekolah - Nur Saqinah Galugu (Psycho Idea, 2019)
Students engagement is a very important variable to support students' academic achievement and success. Previous studies showed that the students who disengage will show a lazy behavior and will mislead them to dismiss their classes and even lead them to stop getting to school.This research aims to give an understanding to all professionals around the students', such as their parents, teachers, and peers about the importance of stimulating the students' motivation  so that they will engage in some particular school activities. The specific purpose of this study is to examine the correlation between the social support and students engagement at school mediated by achievement motivation.This research is a correlational research. The dependent variable (y) is students engagement measured by the school engagement index. While the Independent Variable (x) is a social support measured by using child and adolescents social support (CASS). Veriable mediation is an achievement motivation measured by Achievement Motive Scale. Data were analyzed by using the path analysis method. Participants were  120 students of senior high school number 3 Palopo selected by using the proportional sampling technique.The results showed that there was a significant positive correlation among social support, achievement motivation, and students engagement. While achievement achievement motivation can not be functioned as the mediator on the relationship of social support and student engagement, it is shown from the direct correlation which is greater than the indirect one. The results of this study contribute to the education sector in particular to minimize the students’ disengagement.